Pengaruh Kompetensi, Indepedensi, Pengalaman Kerja, Akuntabilitas, Tekanan Anggaran Waktu Dan Etika Auditor Terhadap Kualitas Audit (Studi pada Kantor Akuntan Publik di Solo dan Semarang) - Khotimah, Khusnul; , Fauzan, SE, M.Si, Akt, CA (2017)
The aims of this research is to find out the effect of the competency, independency, work experience, accountability, time budget pressure and auditor ethics towards audit quality. The population of this research is auditors who work in public accountant office in Solo and Semarang. Method of the data collection is using a purposive sampling technique. The sample used in this research for about 47 respondents. In analyzing the data, this research using multiple regression. The result of the research pointed out that R2 acquired in 0,557 values which mean that 55,7% audit quality influenced by the competency, independency, work experience, accountability, time budget pressure and auditor ethics. The remainder of 44,3% influenced by outer variable. The result of the t experiment pointed out that the competency, independency, work experience, accountability and time budget pressure affecting the audit quality while auditor ethics does not affect the audit quality.